Ethno-botanical and Germinational Aspects of Rauvolfia serpentina (L.) Benth. ex Kurz - Trivedi, M.P.; Kumari, R. (Our Nature, 2012)
Rauvolfia serpentina is a medicinal plant of family Apocynaceae. For centuries since pre-Vedic period it has been used for different medicinal purposes in India and Malaysia. Its preparations have been reported for treatment of fever, snake bite and insanity. DOI: http://dx.doi.org/10.3126/on.v9i1.5750